Taxonomic status of Cyrtoscydmus described by C. Schaufuss from the Philippines (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
In 1891 Camillo Schaufuss described two new species of Cyrtoscydmini from the Philippines and placed them in a genus Cyrtoscydmus Motschulsky, 1870: C. fundaebraccatus and C. manillae. Later authors (e.g., Csiki 1919; Newton & Franz 1998) treated Cyrtoscydmus as a subgenus of Stenichnus Thomson, 1859 and currently these names are synonyms (Meybohm 2004). Csiki (1919) lists the species of Schaufuss as Stenichnus (Cyrtoscydmus) fundaebraccatus and Stenichnus (Cyrtoscydmus) manillae. Since then, the taxonomic status of these species has not been verified.